Impaired disengagement of attention and its relationship to emotional distress in infants at high-risk for autism spectrum disorder. Issue 5 (28th May 2018) - Bryson, Susan; Garon, Nancy; McMullen, Tracey; Brian, Jessica; Zwaigenbaum, Lonnie; Armstrong, Vickie; Roberts, Wendy; Smith, Isabel; Szatmari, Peter
ABSTRACT: Introduction : We provide data on visual orienting and emotional distress in infants at high and low risk for autism spectrum disorder (ASD). Method : Participants included 83 high-risk (HR) infants with an older sibling with ASD and 53 low-risk (LR) control infants with no family history of ASD. Infants were assessed on the gap-overlap task and a parent-completed temperament questionnaire at 6 and 12 months of age. At 36 months of age, an independent, gold standard diagnostic assessment for ASD was conducted. Results : HR infants subsequently diagnosed with ASD were distinguished at 12 months by an asymmetric disengage impairment (for left- vs. right-sided stimuli) that was associated with an increase in latencies between 6 and 12 months. Across groups, prolonged left-directed disengage latencies at 12 months were associated with emotional distress (high irritability and difficult to soothe). Conclusions : The asymmetry in our findings raises the question of whether the disengage problem in ASD is at base one of orienting or alerting attention. Our findings also raise the question of whether attention training might be a critical ingredient in the early treatment of ASD.